Internal audit capability level: case studies of state, state statutory body and public university organizations in Malaysia - Nur Ain Zakiah, Mohd Yusof; Hasnah, Haron; Ishak, Ismail (International Academic Institute for Science and Technology, 2018)
This paper is a part of doctoral degree preliminary study. The primary objective of this paper is to measure the capability level of internal audit units of the different entities of organizations that are state (CSA), state statutory body (CSB) and public university i.e. federal statutory body (CSC). An explanatory case study method was used to collect the data whereby semi structured interviews, questionnaire and document reviews were conducted. From the analysis of internal audit capability matrix using the questionnaire answered by the heads of internal auditor in CSA, CSB and CSC, it is found that internal audit unit in CSA and CSC both obtained capability level 2 (infrastructure) while CSB only achieved capability level 1 (initial). CSA scored the highest KPA percentage which are 82% followed by CSC (76%) and CSB (71%). Factors that may influence these results and further recommendations on advancing to the next level were discussed.